1998
DOI: 10.1086/286213
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Phenotypic Plasticity of Eyespots in the ButterflyBicyclus anynana

Abstract: We use an outcrossed stock and selected lines of Bicyclus anynana in combination with measurements and manipulations of ecdysteroid hormones in early pupae to examine the regulation of eyespot size in adult butterflies. The eyespots on the ventral wing surfaces express adaptive phenotypic plasticity in response to the dry-wet seasonal environments of the butterflies. Larvae reared at low or high temperatures produce adults with small or large ventral eyespots, respectively. Our experiments examine the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 2 publications
5
41
0
Order By: Relevance
“…Previous studies, using hormone manipulation and artificial selection experiments, have demonstrated a functional role of pupal ecdysteroids in the regulation of wing pattern polyphenism, as well as genetic correlations between dynamics of ecdysteroid titres and wing pattern [18,23,34]. Combined, these findings strongly imply an additional level of regulation between the hormone signal and the response of the developmental pathways producing the wing pattern.…”
Section: (B) Phenotypic Responsesmentioning
confidence: 80%
See 3 more Smart Citations
“…Previous studies, using hormone manipulation and artificial selection experiments, have demonstrated a functional role of pupal ecdysteroids in the regulation of wing pattern polyphenism, as well as genetic correlations between dynamics of ecdysteroid titres and wing pattern [18,23,34]. Combined, these findings strongly imply an additional level of regulation between the hormone signal and the response of the developmental pathways producing the wing pattern.…”
Section: (B) Phenotypic Responsesmentioning
confidence: 80%
“…Experimental studies have linked each of these scenarios to polyphenisms, either by direct measurement of titres, titre regulators or sensitivity, or indirectly by hormone manipulation. Examples include Ecd titre changes linked to horn length in beetles [40]; morph-associated differences in JH dynamics in a wing-polymorphic crickets [39]; and differences in the timing of Ecd release between the two wing-pattern morphs of butterflies [18]. However, these studies typically concern the hormonal dynamics under only two environmental conditions, which makes it impossible to discern whether these hormonal changes are continuous or discrete.…”
Section: Discussion (A) Hormone Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that the organization of the eyespot pattern can be better visualized as a nested hierarchical module (i.e., modules within modules; ref. 5), wherein different levels of integration can be identified: (i) the whole eyespot pattern forms one level, because there is more interdependence among individual eyespots than between these and any other pattern elements; (ii) those eyespots on the same wing surface appear to be more strongly coupled than those on different wing surfaces, possibly in association with different ecological pressures (23,55); (iii) within a wing surface, eyespots in close vicinity tend to be more coupled than distant ones (e.g., the mutations Spotty and 3-4 each affect only two adjacent eyespots; see also ref. 5); (iv) in addition, our results demonstrate high potential for independent variation of eyespot size, and thus, some individuality at the single-eyespot level (see also refs.…”
Section: -49)mentioning
confidence: 99%